2017
DOI: 10.2196/publichealth.7054
|View full text |Cite
|
Sign up to set email alerts
|

Whiplash Syndrome Reloaded: Digital Echoes of Whiplash Syndrome in the European Internet Search Engine Context

Abstract: BackgroundIn many Western countries, after a motor vehicle collision, those involved seek health care for the assessment of injuries and for insurance documentation purposes. In contrast, in many less wealthy countries, there may be limited access to care and no insurance or compensation system.ObjectiveThe purpose of this infodemiology study was to investigate the global pattern of evolving Internet usage in countries with and without insurance and the corresponding compensation systems for whiplash injury.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…The lack of demonstrable symptoms characterizing WAD, together with the peculiar context of the legal system, creates a situation in which policyholders may be particularly prone to exaggerate their symptomatology, motivated by the prospect of generous compensations [ 2 , 21 ]. To this regard, it is relevant to consider the discrepancies in chronic whiplash-related disability and compensation seeking across Europe: in those countries where compensation rates for whiplash injuries are high, chronic whiplash is highly prevalent [ 22 ]. In Germany, for instance, WADs represent the most common consequence of road traffic accidents, counting approximately 20,000 cases each year and costing insurance companies more than 500 million euro annually [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of demonstrable symptoms characterizing WAD, together with the peculiar context of the legal system, creates a situation in which policyholders may be particularly prone to exaggerate their symptomatology, motivated by the prospect of generous compensations [ 2 , 21 ]. To this regard, it is relevant to consider the discrepancies in chronic whiplash-related disability and compensation seeking across Europe: in those countries where compensation rates for whiplash injuries are high, chronic whiplash is highly prevalent [ 22 ]. In Germany, for instance, WADs represent the most common consequence of road traffic accidents, counting approximately 20,000 cases each year and costing insurance companies more than 500 million euro annually [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this regard, it is relevant to consider the discrepancies in chronic whiplash-related disability and compensation seeking across Europe: in those countries where compensation rates for whiplash injuries are high, chronic whiplash is highly prevalent [ 22 ]. In Germany, for instance, WADs represent the most common consequence of road traffic accidents, counting approximately 20,000 cases each year and costing insurance companies more than 500 million euro annually [ 22 ]. Similarly, in Italy, it is estimated that the compensation for whiplash-related damages amounts to more than 2 million euro every year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whiplash-related injuries are estimated to account for approximately 80% of all traffic injuries [ 1 ], representing a critical health, social, and economic issue [ 2 ]. For instance, whiplash is in Germany is the most common consequence of road traffic accidents, with approximately 20,000 cases yearly and costing insurance companies more than 500 million euro [ 3 ]. Although the numbers vary significantly across countries, whiplash-related injuries in Europe were estimated to cost annually up to 10 billion euros [ 4 ], with an increment in recent years [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, Cassidy and colleagues (2000) showed that the elimination of financial compensations for pain and suffering was associated with a drop in the number of insurance claims, as well as with a faster recovery [ 10 ]. Similarly, in countries where compensation for late whiplash-related injuries is not formally provided (e.g., Lithuania, Greece), patients rarely develop chronic symptoms [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%